2018
DOI: 10.1177/105678791802700402
|View full text |Cite
|
Sign up to set email alerts
|

The Problem with the Problem of Human Irrationality

Abstract: Despite the widespread social harm that human irrationality causes, irrationality is not considered to be a social problem. This article explores why this is so, argues why irrationality is unlikely to be considered a social problem, and suggests that the best hope for reducing the social harms caused by human irrationality lies with the educational system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…This can make even major future threats seem insufficient motivation for determined action ( Berger, 2009 ). In general, we see these types of typical, and often flawed, decision making patterns in many different contexts of our society ( Eigenauer, 2018 ). For instance, Flyvbjerg (2009) showed that 9 out of 10 transportation infrastructure projects end up in large cost overrun, which did not improve over time, even over a period of 70 years.…”
Section: Introduction: the Challenges Of Human Welfarementioning
confidence: 99%
See 1 more Smart Citation
“…This can make even major future threats seem insufficient motivation for determined action ( Berger, 2009 ). In general, we see these types of typical, and often flawed, decision making patterns in many different contexts of our society ( Eigenauer, 2018 ). For instance, Flyvbjerg (2009) showed that 9 out of 10 transportation infrastructure projects end up in large cost overrun, which did not improve over time, even over a period of 70 years.…”
Section: Introduction: the Challenges Of Human Welfarementioning
confidence: 99%
“…However, there is still lack of insight into how biases play a role in the process of environmental policymaking and how this knowledge may be used to deal with the major systemic challenges that the modern world is confronted with. Despite their possible substantial effects on society and human wellbeing, cognitive biases have never been a serious matter of concern in the social and political domain ( Eigenauer, 2018 ). In this paper, we will therefore analyze the constellation of psychological biases that may hinder behavioral and policy practices addressing sustainability challenges.…”
Section: Introduction: the Challenges Of Human Welfarementioning
confidence: 99%
“…Learning centres across the globe do not realise that they lack the substantive concept of CT, believe that they sufficiently understand it, and assume that they are already teaching it to learners (Baker and Wick, 2019;Eigenauer, 2019;Kasemsap, 2017;Wilson et al, 2015). Lectures notes memorisation, and (largely ineffective) short-term study habits are still the norm in teaching and learning today, with the horrific ramifications of mass production of "knowledge-gap in practice graduates" (Flores et al, 2010;Heijltjes, Gog and Paas, 2014).…”
Section: Introductionmentioning
confidence: 99%